Values-based multinational management : achieving enterprise sustainability through a human rights strategy - Tavis, Lee A. (Book collections on Project MUSE., 2009)
In this volume, Lee Tavis and Timothy Tavis contend that the values dimension of the actions of multinational firms is becoming increasingly important, given the worldwide integration of economies and peoples.